Length-Weight Relation of Condition Factors of Barb (Barbonymus balleroides Val. 1842) in Serayu River, Central Java - Norce Mote (Jurnal Perikanan dan Kelautan, 2016)
The Serayu River, a major river in Central Java Province, crosses five regenciesincluding Banjarnegara Regency. Barb is one of the fish species, which found inthe Serayu River tends to decrease in population. The aim of The Study are toexamine length-weight relationship and condition factor of barb (Barbonymusballeroides Val. 1842) in Serayu River. The fish samples were taken from October2012 to March 2013. Fish samples were caught using nets, gill nets. The sampleswere analyzed to find out the length, weights and condition factor. The resultsshowed That length weights relationshipis expressed by the equation: W = 3E-05L2.81 and allometric negative, while the female fish W = 8E-06L3.05 andallometric positive. the condition factor male fish peak season in March andfemale fish in October. The need for gear restrictions and arrests during peakreproductive season in October.